Aluminum-induced changes in cell-wall pectin methylesterase activity of wheat seedlings in relation to their aluminum tolerance - TANG Jian-feng; LUO Hu-xu; LIN Xian-yong; ZHANG Yong-song; LI Gang (浙江大学学报. 农业与生命科学版)
The effects of aluminum (Al) on root elongation and changes in cell wall pectin methylesterase (PME) activity in the roots of Al-resistant (Xiaimai-1) and Al-sensitive (Fu-84) genotypes of wheat (Triticum aestivum L.) were examined. Root elongation was inhibited in both genotypes when wheat roots were exposed to 30 µmol·L-1 AICI3 solution for 6 h or 24 h, the inhibition of root elongation being more prominent in the Al-sensitive genotype (Fu-84). Al content was significantly higher in 0-10 mm root segments than that in 10-20 mm root segments; and more Al accumulated in Fu-84 than in Xiaimai-1 in 0-10 mm root segments. Pectin uronic acid content in Fu-84 was higher than in Xiaimai-1 in 0-10 mm root segments, which was increased under Al stressed condition, more conspicuously in the Al-sensitive genotype Fu-84. The PME activity in roots of Xiaimai-1 was less affected by Al treatment, the PME activity in 0-10 mm root segment of Fu-84 was increased when the duration was 6h and was decreased when the duration was 24h. The root tip (0-10 mm root segment) cell wall PME activity in Fu-84 was enhanced after 6h Al treatment but decreased after 24 h Al treatment. Whether the plant was treated by Al or not, the Al-sensitive genotype Fu-84 always showed a higher cell wall PME activity than did the Al-resistant genotype Xiaimai-1 in 0-10 mm root segment. The Al-sensitive genotype Fu-84 always showed a higher PME activity and the activity of PME and pectin content increased after short-term exposure to Al, which results in more Al binding sites in Fu-84 than in Xiaimai-1. The present data emphasize the importance of the cell wall PME activity for the manifestation of Al toxicity and resistance.